The core concepts of occupational therapy : a dynamic framework for practice - Creek, Jennifer (Jessica Kingsley, 2010)
The profession of occupational therapy has a highly specialised language, but until now there have been no standard definitions of its key terms. Based on the work of the terminology project group of the European Network of Occupational Therapy in Higher Education (ENOTHE), this book selects and defines the core building blocks of occupational therapy theory. Consensus definitions of a wide range of terms are developed through an analysis of published definitions from around the world. Concepts with similar meanings are clustered into groups, and the clusters are then arranged into a conceptua.